Supratentorial Atypical Rhabdoid Teratoid Tumor – A Case Report - Mesquita Filho, Paulo Moacir; Vartha, Ana Paula Pompeo; De Carli, Fernanda; Manfroi, Gregori; De Cesaro, Marcelo Pedrotti; Oro, Carlos Eduardo Bier; Figini, Vitório Ávila; Azambuja Júnior, Nério Dutra; Beck, Adriana Eli; Schwingel, Daniela (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Atypical rhabdoid teratoid tumors (ARTTs) are rare embryonic tumors, usually localized in the posterior fossa and diagnosed in children under 3 years-old. The treatment includes surgical resection, radio and chemotherapy, and the prognostic is unfavorable, with an average median survival of 1 year. We present the case of a 3-year-old patient, with history of headache and vomiting, followed by absence seizures, temporal automatism, syncope accompanied by sialorrhea and sphincteric loss succeeded by a postictal period. Surgical excision was performed and the anatomopathological study confirmed ARTT. The ARTTs are embryonic tumors, a category in which medulloblastoma and primitive neuroectodermal tumors (PNETs) represent the most common central nervous system (CNS) malignancies in childhood.
Keywords: atypical rhabdoid teratoid tumor; embryonic tumors; malignancies in childhood; neuroectodermal tumors